2019
DOI: 10.2139/ssrn.3489435
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality in Macro-Financial Dynamics

Abstract: We estimate the evolution of the conditional joint distribution of economic and financial conditions in the United States, documenting a novel empirical fact: while the joint distribution is approximately Gaussian during normal periods, sharp tightenings of financial conditions lead to the emergence of additional modes-that is, multiple economic equilibria. Although the U.S. economy has historically reverted quickly to a "good" equilibrium after a tightening of financial conditions, we conjecture that poor pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Focusing on US data, they have found that the lower quantiles of GDP growth vary with financial conditions while the upper quantiles are stable over time, therefore pointing to an asymmetric and nonlinear relationship between financial and real variables. Adrian et al (2018) have confirmed this result extending the sample to different countries and have pushed this view further by defining the concept of growth at risk as GDP growth at the lower fifth percentile of the GDP growth distribution, conditional on an index of financial stress. Building on this work, several recent papers have explored the idea, while policy institutions have adopted the methodology to monitor risk in different countries (see, for example, Prasad et al, 2019 for a description of the use of this method at the IMF).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Focusing on US data, they have found that the lower quantiles of GDP growth vary with financial conditions while the upper quantiles are stable over time, therefore pointing to an asymmetric and nonlinear relationship between financial and real variables. Adrian et al (2018) have confirmed this result extending the sample to different countries and have pushed this view further by defining the concept of growth at risk as GDP growth at the lower fifth percentile of the GDP growth distribution, conditional on an index of financial stress. Building on this work, several recent papers have explored the idea, while policy institutions have adopted the methodology to monitor risk in different countries (see, for example, Prasad et al, 2019 for a description of the use of this method at the IMF).…”
Section: Introductionsupporting
confidence: 55%
“…The appeal of this approach to policy work is that it provides a framework in which forecasting can be thought of as a risk managing exercise (see Kilian and Manganelli, 2008 for the first development of this idea). This is the core idea of what is referred to as the Growth at Risk (GaR) framework of Adrian et al (2018). 1 A separate line of research pioneered by the BIS has stressed the importance of the leverage cycle as an indicator of risk, while several studies have pointed at a correlation of excess growth in leverage and financial crisis (see Jorda et al, 2011, Schularick andTaylor, 2012, Jorda et al, 2013 and related literature) and found that recessions preceded by financial crises are deeper and followed by slower recoveries (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In this example, the 95 percent quantile of the predictive distribution changes relatively little, with values of 1.65 in period 1 and 1.29 in period 2. The 5 percent quantile drops significantly, from -1.65 in period 1 to -5.29 in 4 Jensen, et al (2020) also develop a dynamic stochastic general equilibrium model consistent with their empirical findings. Adrian, et al (2020) extend an econometric formulation of a DSGE model to include endogenous risk.…”
Section: Introductionmentioning
confidence: 70%
“…time, which they link to the increased financial leverage of households and firms. 4 At a practical level, monetary policymakers have commonly treated forecast distributions as being potentially asymmetric, at least at some points in time. The Bank of England's well-known fan charts for inflation are constructed with a two-piece normal distribution to reflect asymmetries as judged by the Monetary Policy Committee.…”
Section: Introductionmentioning
confidence: 99%
“…1 Earlier work of Manzan (2015) used quantile regression to assess the value of a large number of macroeconomic indicators in forecasting the complete distribution of some key variables. 2 The interest in tail risks reflects an underlying perception or assumption of asymmetries in distributions of outcomes. Some form of asymmetry has long been incorporated in particular economic models (e.g., Markov switching or threshold models; in a recent example, Alessandri and Mumtaz (2017) use threshold models to assess output forecasts in periods of financial distress).…”
Section: Introductionmentioning
confidence: 99%